Genetic basis of barley contributions to beer flavor. (March 2022) - Sayre-Chavez, Brooke; Bettenhausen, Harmonie; Windes, Sarah; Aron, Patricia; Cistué, Luis; Fisk, Scott; Helgerson, Laura; Heuberger, Adam L.; Tynan, Sean; Hayes, Patrick; Muñoz-Amatriaín, María
Abstract: Barley malt is critical for the malting, brewing, and distilling industries, as it is one of the main ingredients of beer and some types of spirits. There is growing evidence that barley genotype - via malt - can impact the flavors of beers and spirits. However, information on the barley genes involved in these flavors is lacking. Therefore, we used quantitative trait locus (QTL) mapping of malt quality traits, beer sensory descriptors and metabolic compounds on a biparental population of doubled haploids derived from the cross of the cultivars Golden Promise and Full Pint. Putative candidate genes for QTLs were identified by alignment with the reference barley genome sequence. There were thirty-seven QTLs across all chromosomes except 4H, with three QTL clusters located on 3H (1 cluster) and 5H (2 clusters: mid-5H and end-5H). Those "hotspots" contained QTLs for multiple phenotypes. Several candidate genes that regulate plant metabolism were identified within the QTLs and included HvAlaAT, HvDep1, HvMKK3, HvGA20ox1 and HvGA20ox2. These genes are involved in seed dormancy and plant height. Alleles at these loci, and perhaps at physically linked loci, can have key downstream effects on malting quality, beer flavor, and abundance of volatile metabolites. Graphical abstract: Image 1 Highlights: QTLs and candidate genes were identified for malting quality, beer sensory, and beer metabolomics traits. Candidate genes for QTLs include genes related to grain dormancy and plant height. Future directions for barley contributions to beer flavor research are highlighted.